2021
DOI: 10.4103/jfmpc.jfmpc_885_21
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Down’s syndrome on oral health status in patients

Abstract: Background: Down syndrome which is also known as “trisomy 21” is the commonest chromosomal defect that has been associated with intellectual disability or impairment. Clinically, it has been characterized by the generalized presence of hypotonic musculature, variety of neurobiological alterations, numerous respiratory diseases, and significantly higher risk of developing infection along with various dental abnormalities and oro-facial dysmorphological changes. Periodontal diseases are the most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…This is because of physical features that people with ID have, such as low muscle tone, loose ligaments that require greater joint flexibility and decreased joint strength which would make it challenging to maintain dental hygiene or reduce access to dental treatments for this population group 20 . These findings were in accordance with past works that evaluated gingivitis in ID patients 20,21 . However, different findings contradict Amira et al 10 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is because of physical features that people with ID have, such as low muscle tone, loose ligaments that require greater joint flexibility and decreased joint strength which would make it challenging to maintain dental hygiene or reduce access to dental treatments for this population group 20 . These findings were in accordance with past works that evaluated gingivitis in ID patients 20,21 . However, different findings contradict Amira et al 10 .…”
Section: Discussionsupporting
confidence: 84%
“…20 These findings were in accordance with past works that evaluated gingivitis in ID patients. 20,21 However, different findings contradict Amira et al 10 who reported that patients with ID have lower moderate gingivitis. 22 This might be explained by different demographic characteristics and divergent socioeconomic status.…”
Section: Gingivitis In People With Idmentioning
confidence: 94%
“…altered neutrophil chemotaxis, reduced T cell function and inadequate antibody production) is probable and remains to be studied 45,47 . A recent study in 100 DS children, reported high plaque and calculus indices 48 . In this systematic review, plaque accumulation was increased in DS individuals but meta‐analysis of this variable was not possible due to different scores used and/or because was not properly reported (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…45,47 A recent study in 100 DS children, reported high plaque and calculus indices. 48 In this systematic review, plaque accumulation was increased in DS individuals but meta-analysis of this variable was not possible due to different scores used and/or because was not properly reported (Table 1). Inadequate plaque control in DS subjects is the result of the phenotype in which the concave profile, malocclusion, tooth abnormalities, mouth breathing, macroglossia and reduced fine motor capabilities are characteristic.…”
Section: Discussionmentioning
confidence: 95%
“…One of the main difficulties in the DS population is oral health maintenance [ 17 ]. DS populations have a higher risk of oral diseases such as dental caries, periodontal disease, and abnormalities of the tongue and palate [ 17 , 18 , 19 ]. This increased risk is associated with various factors, including altered immune function, structural abnormalities of the teeth and jaws, and difficulty with oral hygiene self-care [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%